Peningkatan Keterampilan Refleksi Diri Peserta Didik melalui Circle time untuk Pengelolaan Sosial Emosional - Ajeng Anisatu Rahmah; Nugraha Permana Putra; Nila Novi Marliana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is based on difficulties in building relationships and difficulties in providing empathy towards peers. This research aims to improve students' self-reflection skills through implementing circle time activities for social emotional management using the Classroom Action Research (CAR) method with two cycles. Each cycle consists of planning, implementation, observation and reflection stages. The research involved 24 sixth grade students. Data was collected through observation sheets and interviews with teachers. The research results showed a significant increase in students' self-reflection and emotional regulation skills after participating in circle time activities in both cycles. These findings demonstrate the effectiveness of circle time in supporting social emotional development in the classroom environment